Gambaran kualitas hidup lansia pemakai gigi tiruan lepasan (Observasi pada Sasana Tresna Werdha Ria Pembangunan) - Augusty, Sheilaz; Ayu Ratih Utari Mayun, I Gusti (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Along with age, the prevalence of tooth loss will increase. As a result of tooth loss, treatment in the form of dentures is required. The use of removable denture has a huge impact and benefit on the quality of life. The quality of life in the elderly is very important to know so that the problems that occur in the elderly using removable denture can be evaluated later. Aims: To identify the overview of the elderly quality of life in the use of removable denture. Methods: This is an observational descriptive study with a cross-sectional research design. The study was conducted by distributing GOHAI questionnaires to 21 elderly at the Sasana Tresna Werdha RIA Pembangunan, East Jakarta. Results: The results of the descriptive statistical test show that overall the majority respondents has a moderate quality of life. Based on gender grouping, it was found that the male elderly group had a moderate quality of life, the female elderly group had a moderate quality of life. Then, the 60-74 year old group has a good quality of life, the 75-90 year old group has an moderate quality of life and the over 90 year old group has a moderate quality of life. Then in the category of education level, the majority of respondents are at SMA/SLTA and have a good quality of life. Conclusion: The elderly at Sasana Tresna Werdha RIA Pembangunan have a moderate quality of life.